Analysis of elementary school teachers' perspectives in the Bekasi area on the use of artificial intelligence in Learning - Fairuz Zulia Muntaha; Rizki Hikmawan (Universitas Papua, 2026)
This study shows how elementary school teachers in Bekasi see the use of Artificial Intelligence (AI) in their teaching. It focuses on three key areas: knowing about digital rights, who owns the things created with AI, and which AI models teachers prefer. The research used a quantitative method, asking 394 teachers chosen through purposeful sampling. Data was gathered using well-tested questionnaires and analyzed with SPSS, using methods like descriptive stats, Pearson correlation, and multiple linear regression. The findings show that all three factors have a positive and strong impact on how teachers view AI in education (with a significance level less than 0.05), with digital rights knowledge being the most important. The findings indicate that teachers' readiness to adopt AI is influenced not only by technical skills but also by an understanding of digital ethics and law. In conclusion, teacher capacity development needs to combine technical and ethical training, along with policy and infrastructure support, to encourage the responsible and sustainable use of AI.